The archaeology of inequality (Albany)
xiv, 377 sayfa
Keywords: “The Archaeology of Inequality explores the different aspects of social boundaries and articulation by comparing several interdisciplinary approaches for the analysis of the archaeological data, as well as actual case studies from the Prehistory to the Classical world. The book explores slavery, gender, ethnicity and economy as intersecting areas of study within the larger framework of inequality and exemplifies to what degree archaeologists can identify and analyze different patterns of inequality.” --